Tramadol or paracetamol do not effect the diagnostic accuracy of acute abdominal pain with significant pain relief - a prospective, randomized, placebo controlled double blind study - Oguzturk, H.; Ozgur, D.; Turtay, M. G.; Kayaalp, C.; Yilmaz, S.; Dogan, M.; Pamukcu, E. (Verduci Publisher, 2012)
OBJECTIVES: To examine the effects of early administration of analgesics in patients with acute abdominal pain on pain severity, abdominal findings and diagnostic accuracy. METHODS: 210 patients with non-traumatic acute abdominal pain lasting less than 72 hours were enrolled to this trial. Patients were administrated by placebo, tramadol (1 mg/kg), or paracetamol (15 mg/kg) randomly after the first evaluation of pain severity scores (standard 100 mm visual analog scale) and abdominal findings (rebound, rigidity, tenderness). After 20 and 40 minutes of administrations, pain severity scores and abdominal findings were re-examined. Complete blood count, electrocardiography, plain abdominal x-ray, urine analysis and abdominal ultrasound were used for the initial diagnosis. The final diagnoses were decided after re-examinations, biochemical blood analysis, abdominal computed tomography in all patients and consultations or other diagnostic methods when necessary. RESULTS: There were 70 patients in each group. Baseline pain severity scores and abdominal findings were similar at all groups. After 20 minutes, pain severity scores were decreased in tramadol and paracetamol groups compared with the placebo group as 55% and 45% vs 1% respectively (p < 0.001). After 40 minutes, decreases on pain severity scores were more significant at treatment groups, 67% and 60% vs 0 (p < 0.001). When compared to placebo tramadol and paracetamol increased the new onset or worsening nausea or vomiting. There was no difference on abdominal findings among the groups after 20 and 40 minutes examinations. Diagnostic accuracy of tramadol, paracetamol and placebo groups were 96%, 94% and 94% respectively. CONCLUSIONS: Early administration of tramadol and paracetamol provided effective pain relief in patients with non-traumatic acute abdominal pain and those administrations did not interfere with diagnosis.
Keywords: Emergency Department; Abdominal pain; Tramadol; Paracetamol